Development of efficient formulation for the removal of iron sulphide scale in sour production wells. (19th June 2018) - Mahmoud, Mohamed; Hussein, Ibnelwaleed A.; Sultan, Abdullah; Saad, Mohammed A.; Buijs, Willem; Vlugt, Thijs J. H.
Abstract: Iron sulphide scale, which exists in different forms, is common in sour oil and gas production wells. Iron sulphide hard scales are difficult to remove with acids, requiring mechanical intervention or the replacement of the production tubing. An environmentally friendly formulation with a high pH is proposed for the removal of both soft and hard iron sulphide scale from oil and gas wells. The formulation consists of DTPA (di‐ethylene tri‐amine penta acetic acid) in addition to K2 CO3 as a catalyst. High pressure high temperature solubility experiments were performed under both static and dynamic conditions in the temperature range of 70–150 °C and a constant pressure of 3447.38 kPa. Several combinations of the catalyst and DTPA chelating agent were used to optimize the catalyst/DTPA ratio to achieve maximum scale solubility. Field scale samples were collected and analyzed using XRD. The scale removal efficiency of the proposed formulation outperforms that of the current formulations used in the oil industry, with the added advantage of not releasing H2 S. The optimum DTPA concentration is 20 wt% and the optimum catalyst concentration is 9 wt%, which provides a solubility of 90 % of the field scale. In addition, the ecotox profile of the proposed formulation is better than that of the currently used formulations because toxic corrosion inhibitors are not used. The maximum reported corrosion rate for the new formulation is 0.036 kg/m 2, which is well below the acceptable limit (< 0.227 kg/m 2 ).